EVALUASI KERUSAKAN AKIBAT GEMPA PADA BANGUNAN GEDUNG BANK ACEH CABANG SIGLI - Samsunan Samsunan (Universitas Teuku Umar, 2016)
Aceh is one of the areas in Indonesia most quake susceptible. Earthquake zoning map issued by the Minister of Public Works in 2010 showed that the Aceh region to earthquakes susceptible. The earthquake susceptible affecting the condition of existing building, while design and construction was built before earthquake zoning map to release. One of which is Bank Aceh building have in experience damage due January 22, 2013 an earthquake measuring 6.0 on the Richter scale, where some of the structural elements of the building experience crack. For this purpose analysis and evaluation of the damage to buildings affected of earthquake. The evaluation was done by reviewing directly into the field and collecting primary data and secondary data. Analysis of the strength of concrete is done by using the Concrete Hammer Test. The results showed that the buildings experience cracks on the beams. The results of the evaluation and assessment analysis, the building belongs in the level of minor damage and is still fit for use with some partial improvement and minor repairs. Minor repairs need to be done on the architectural and non- structural element. While the structural elements necessary repairs being in some parts of the beams and columns. Keyword: damage of building, earthquake, Bank Aceh